일부 성인의 치과위생사의 이미지에 미치는 영향요인 - 박시현(Si-Hyeon Park); 강민이(Min-i Kang); 김다현(Da-Hyun Kim); 김윤희(Yun-Hee Kim); 김태희(Tae-Hee Kim); 손아름(A-Reum Son); 유송현(Song-Hyeon Yoo); 김유린(Yu-Rin Kim) (한국구강보건과학회지, 2021)
Objectives: This study is intended to be used as basic data to enhance the image of dental hygienists by confirming the effect of the importance of dental hygienists on the image of dental hygienists. Methods: Hierarchical regression analysis was performed to determine the effect of dental hygienist importance and dental visit intervals on the dental hygienist image step by step. Results: As factors influencing the dental hygienist image, the younger, the more office workers, the shorter the dental visit interval. the higher the importance of the dental hygienist, the more significant the influence on the dental hygienist image was confirmed. Conclusions: In order to establish a professional image of dental hygienists, we expect continuous publicity that can increase the importance of dental hygienists and an increase in occupational ethics awareness that can increase the professional value of dental hygienists themselves. KCI Citation Count: 1